Evaluation of Differing Genetic Potentials on Beef Cattle Resource Use in the Great Plains - A. D. Lakamp; D. G. Aherin; R. L. Larson; I. A. Ciampitti; C. J. Kopsa; R. L. Weaber; J. M. Bormann; M. M. Rolf (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to examine the environmental impact and efficiencies of beef cattle with differing genetic potentials in the Great Plains. Study Description:A 100-head cow-calf herd was simulated for 74 different land regions and six combinations of genetic potential within regions: large, moderate, or small mature size and high (24.2 lb/day) or low (17.6 lb/day) milk production. The simulation determined the average amount of feed required to maintain the herd. Land, water, and methane production were estimated for each combination of land use area and genetic potential. Weaning weight was estimated for each genetic potential to find resource use efficiency. The Bottom Line:Animals with greater energy requirements have larger environmental footprints. However, in environments where nutritional availability is not restricted, small, high milking cattle likely have the smallest environmental footprint per pound of weaned calf.
Keywords: sustainability; beef cattle; water footprint